Understanding digital image processing using matlab - Manza, Ramesh; Patwari, Manjiri B.; Rajput, Yogesh M.; Rathod, Deepali (Navi Mumbai Shroff Publishers, 2016)
Understanding of digital image processing using MATLAB is a book for a course of Image Processing using Matlab along with techniques for developing GUI and to covers few advanced topics. The emphasis is given on how to process the image start from basics to advanced level and design GUI in Matlab software for user applications. This book will help to learn about how to do image processing and to develop user friendly and more interactive GUI in Matlab with the help of basic tool along with programming, graphical user interface and image processing techniques. Every chapter begins with introductory remarks about its contents. The measure contents of all chapters consist of theory, syntax and example along with developed GUI. Every chapter is ended with detail summary and exercise for the reader. User can get benefited from the given set of exercises to do mastery in digital image processing.
Keywords: EXTC Engineering